Pin-on-disc study of a friction material dry sliding against HVOF coated discs at room temperature and 300 °C. (November 2017) - Federici, Matteo; Menapace, Cinzia; Moscatelli, Alessandro; Gialanella, Stefano; Straffelini, Giovanni
Abstract: The tribological behavior of a commercial semi-metallic friction material dry sliding against an uncoated cast iron disc and HVOF coated discs at room temperature and at 300 °C has been investigated. Two types of coatings were investigated, based on Cr3 C2 -NiCr and WC-CoCr systems. The tests were carried out using a pin-on-disc apparatus. The characteristics of the friction layer that forms on the worn surfaces of the friction material (the pin) and on the counterface disc were analyzed and correlated with the friction and wear behavior of the couplings. At room temperature, quite a long initial stage was observed, required to form a compact friction layer and to achieve a constant average friction coefficient. At 300 °C, steady-state conditions are attained almost from the beginning of the test. The wear rates of the friction materials are mild at room temperature and close to severe at 300 °C because of the thermal softening of the friction material. The wear rates of the coated discs are always negligible, since the contact temperature is not sufficiently high to induce a softening or an oxidative damage of the coatings. Although referring to rather simplified testing conditions, the results obtained in this study provide useful indications on the possibility of using HVOF coatings in braking systems to reduce not only their wear but also, most importantly, the release of particulate matter in the environment. Highlights: Wear of coated discs is always negligible. Wear of pins is mild at RT and increases very much at 300 °C. At 300 °C, the formation of a wide and thick friction layer is observed. At 300 °C, steady-state conditions for friction and wear were reached soon.